The Effect of Leadership Style and Compensation on Employee Performance with Organizational Commitment - Zulfa Nurfauziah, Hasna; Kusuma Chandra Kirana; Epsilandri Septyarini; Azmah Othman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The purpose of this study was to determine the effect of leadership style and compensation on employee performance through organizational commitment as an intervening variable. This study uses primary data and is quantitative in nature. The population in this study were all employees of Baitul Maal Wa Tanwil, Gunungkidul Regency, while the sample used was 100 people. Sampling technique used in this research is sampling technique, random sampling and hairs theory with Structural Equation Modeling analysis method. The analysis used in this research is path analysis, hypothesis testing, multiple linear regression and single test. This study indicate that employee performance is getting better if the influence of leadership style and compensation is better preceded by the creation of a higher organizational commitment that individuals have to their organization. This is because leadership style has a positive effect on commitment, but has no effect on performance. Compensation has no effect on commitment but has a positive effect on performance. While commitment has a positive effect on performance so that it can be a mediator between leadership style and employee performance, not on employees.